Membangun Perdamaian Pasca Konflik - Fitriani, Fitriani; Husaini, Alpahmi (Da'watuna: Journal of Communication and Islamic Broadcasting, 2023)
After the peace agreement, Indonesia is now in the post-conflict era and many conflicts in various regions of Indonesia have decreased. Democratization and decentralization bring about improvements in social, economic and security conditions in society. This paper discusses post-conflict challenges in various regions of Indonesia. The main focus of this paper is approaches and strategies for post-conflict peacebuilding in order to build a foundation for peace to achieve consolidation of peace and sustainable development. economics, education and law. The third sector is the main focus of development in order to overcome the root of the conflict. As well as the establishment of institutions (FKUB), FKDM and FPK, as a responsive step by the government in detecting social conflicts in society. The success of all levels of post-conflict management is still dominated by the state, and this is the weakness of the post-conflict management being carried out, due to the dominance of state actors, with minimal involvement/involvement from civil society. Keywords: post conflict; peace building; sustainable development